Readmission Patterns to KMPT Acute Wards - Olubunmi Olure; Valsraj Koravangattu (BJPsych Open, 2025)
Aims: To identify patterns of readmission to acute wards and look for specific themes associated with readmissions – discharge planning, diagnosis, gender, social support, accommodation issues and any other associations.